(3cTGa GdbfGY Yf GdEbfGYs - (3efUhQ Hf jhfS Hf UdGM GdOjf GHf MSf Hf EOQjS GdHghJj GdMfHdj , J (B1051 (3g` s; (3ehSi Hf CMeO Hf ehSi Hf SGde Hf YjSi Hf SGde GdnMnqLGhj GdebOSj, Ke GdUGdMj, TQa GdOjf, CHhGdfLG,J (B968 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf CLd GdYdhe bOQkG hGYdGgG aNQkG hGHdZgG aVjdI s
(3BNQgG (B:s
(3hdG jCPf GdeSde dRhLJg GdfUQGfjI Ch GeJg cPdc Ch GeJg cPdc Cf JNQL Edi YjO Ch JPgH Edi HjYI hdg Cf jefYgG s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B320 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B34s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B353s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs